Minimum clearance technology to improve performance of twin-screw refrigeration compressors by spraying coating on rotors. (August 2021) - Sun, Shizhong; Li, Yanpeng; Chen, Wenqing; Xing, Ziwen; Liu, Hua
During the operating of twin-screw refrigeration compressors, the leakage has a significant influence on the performance of compressors. In this paper, a novel minimum clearance technology that applies the abradable coating to the rotor surface is proposed to lessen the leakage. In order to adapt to the application of the abradable coating, the deformation of rotors during operation is analyzed and a suitable clearance is designed based on the fluid-solid coupling analysis. Then, a suitable coating pre-treated by sandblasting is obtained according to the results of friction coefficient and abradability test. Finally, a prototype is tested and the total efficiency, volumetric efficiency, refrigerating capacity, and COP of the prototype are compared before and after spraying the coating. Test results show that the volumetric efficiency and refrigerating capacity increase significantly after spraying the abradable coating, and the input power decreases slightly. As a result, the COP increases by 6.71% and 7.89% at two nominal operating conditions.